Host-Specific Serum Factors Control the Development and Survival of Schistosoma mansoni - Anisuzzaman,; Frahm, Sören; Prodjinotho, Ulrich Fabien; Bhattacharjee, Sonakshi; Verschoor, Admar; Prazeres da Costa, Clarissa (Frontiers in Immunology, 2021)
Introduction: Schistosomiasis is a neglected tropical disease (NTD) caused by blood-dwelling flatworms which develop from skin-penetrating cercariae, the freely swimming water-borne infective stage of Schistosoma mansoni, into adult worms. This natural course of infection can be mimicked in experimental mouse models of schistosomiasis. However, only a maximum of 20-30% of penetrated cercariae mature into fecund adults. The reasons for this are unknown but could potentially involve soluble factors of the innate immune system, such as complement factors and preexisting, natural antibodies. Materials and Methods: Using our recently developed novel serum- and cell-free in vitro culture system for newly transformed schistosomula (NTS), which supports long-term larval survival, we investigated the effects of mouse serum and its major soluble complement factors C1q, C3, C4 as well as preexisting, natural IgM in vitro and assessed worm development in vivo by infecting complement and soluble (s)IgM-deficient animals. Results: In contrast to sera from humans and a broad variety of mammalian species, serum from mice, surprisingly, killed parasites already at skin stage in vitro. Interestingly, the most efficient killing component(s) were heat-labile but did not include important members of the perhaps best known family of heat-labile serum factors, the complement system, nor consisted of complement-activating natural immunoglobulins. Infection of complement C1q and sIgM-deficient mice with S. mansoni as well as in vitro tests with sera from mice deficient in C3 and C4 revealed no major role for these soluble factors in vivo in regard to parasite maturation, fecundity and associated immunopathology. Rather, the reduction of parasite maturation from cercariae to adult worms was comparable to wild-type mice. Conclusion: This study reveals that not yet identified heat-labile serum factors are major selective determinants of the host-specificity of schistosomiasis, by directly controlling schistosomal development and survival.